Gibberellic Acid Levels and Quality Effects of Gibberellic Acid in Treated Table Grapes - Wolf, E.E.H.; Loubser, J.T. (South African Journal of Enology and Viticulture, 2017)
Sultanina and Waltham Cross vineyards were treated with increasing dosages and late applications of gibberellic acid. Berries with sampled at different stages after treatment as well as after four weeks' cold storage. The gibberellic acid levels of treated and untreated berries were determined using a gibberellic acid-specific radio-immunoassay. Irrespective of treatment, late applications and high dosages increased gibberellic acid levels in berries at harvest but did not exceed the 200 ng/g fresh berry mass maximum limit. The effects of treatments on bunch quality, i.e. ripeness, berry size, berry crack, berry shatter, decay, S02 damage, colour, blemishes, even berry size, straggliness and dry stems were also determined. Berry ripening was delayed and blemishes were induced by high GA dosages and late GA applications.